Coronary artery vasospasm and cardiogenic shock as the initial presentation for eosinophilic granulomatosis with polyangiitis. Issue 4 (April 2016) - Bitar, Abdallah Y.; Thompson, Caleb D.; Tan, Christina W.; Allem, Kavitta; Khachatrian, Aelita; Weis, Peter J.; Garg, Vikram; Srivastava, Ajay
Abstract: A 68-year-old woman presented to our hospital with unstable angina and was admitted for further evaluation. While hospitalized, she developed persistent angina with hypotension along with ST-segment elevation in leads V1 –V2 along with lead aVR elevation on 12-lead electrocardiogram. Coronary angiography revealed diffuse multi-vessel coronary vasospasm most notably in the left anterior descending artery (LAD). Due to incomplete resolution of vasospasm with intracoronary verapamil and nitroglycerin, along with hemodynamic compromise requiring an intra-aortic balloon pump, percutaneous coronary intervention (PCI) of the LAD was performed. Clinical workup revealed hypereosinophlia and elevated IgE; diagnosis of eosinophilic granulomatosis with polyangiitis was confirmed with evidence of radiographic migratory pulmonary infiltrates and airway obstruction on spirometry. The patient had recurrent angina after PCI but her symptoms resolved fully after a course of corticosteroids. We attribute her refractory vasospastic angina to previously undiagnosed small/medium-vessel vasculitis. <Learning objective: We present a case of refractory coronary artery vasospasm in the setting of eosinophilic granulomatosis with polyangiitis (EGPA). Typically, calcium channel blockers and nitrates are used to treat hyperreactive narrowing of the coronary vasculature but we propose this case was refractory to standard treatment due to the underlying pathology of EGPA. Alternative causes of coronary vasospasm when standard therapies fail should be considered.>